The positive aspects of caregiving in dementia: A scoping review and bibliometric analysis - Wang, Jun; Li, Xuelian; Liu, Weichu; Yang, Bing; Zhao, Qinghua; Lü, Yang; Xiao, Mingzhao (Frontiers in Public Health, 2022)
Purpose The increasing incidence of dementia and home-based care exposes family caregivers to a variety of challenges as they endure strong stressors underlying the caregiver role. Despite growing publications on positive aspects of caregiving in dementia, few studies have identified the extent, nature, and gaps in the existing literature based on a holistic view. The aim was to identify key issues and a holistic view of literature regarding positive aspects of caregiving in dementia. Methods A scoping review was conducted underlying a five-stage framework by Arksey and O'Malley. Five databases, including PubMed, CINAHL, PsycINFO, Embase, and Web of Science, were searched, and references were listed accordingly. Data were extracted by two researchers, comprising article characteristics, forms of positive aspects of caregiving and measurements, theories, forms of dementia and family caregiver, and keywords. Descriptive statistics and narrative synthesis were performed to analyze data. Network analysis of keywords and authors was conducted using VOSviewer software. Word cloud analysis of titles was examined by NVivo. Results The review included 230 articles, most of which have been published in the last decade (62.61%). Most articles (40.00%) were contributed by the United States. Cross-sectional studies (41.30%) ranked first, followed by qualitative studies (13.48%). Over a quarter of the literature (28.26%) focused on Alzheimer's care, and nearly 90% included all forms of family caregivers. The Positive Aspects of Caregiving Scale and stress coping theory were most frequently cited. Four clusters dominated by Casey D, Quinn C, Joling KJ, and Teahan A were identified in the network of co-authorship. Six themes were identified: current situations of caregiver experiences, antecedents, consequences, measurement development, effects of interventions, and the concept of positive aspects of caregiving. These were in line with network analysis of keywords and word cloud analysis of titles. Conclusions Positive aspects of caregiving in dementia have been widely concerned, but most of them are based on the theory of the negative stress process and are limited to current situations and influencing factors. Building theories focus on the positive aspects of caregiving, subsequently developing a comprehensive measurement and effective interventions, should be further studied.